A cyclic azapeptide ligand of the scavenger receptor CD36/SR-B2 reduces the atherosclerotic lesion progression and enhances plaque stability in apolipoprotein E-deficient mice - Jade Gauvin; Geneviève Frégeau; Hanan Elimam; Hanan Elimam; Hanan Elimam; Liliane Ménard; David Huynh; Catherine Lê; Ahsanullah Ahsanullah; Ahsanullah Ahsanullah; William D. Lubell; Huy Ong; et al. (Frontiers Media S.A., 2023)
Atherosclerosis is a chronic inflammatory disease of the arterial walls that develops at predisposed sites. As a major risk factor for adverse cardiovascular pathology, atherosclerosis can progress to myocardial infarction and stroke, due to the rupture of unstable atherosclerotic lesions. Macrophage uptake of modified lipoproteins and metabolic dysfunction contributes significantly to the initiation and development of atherosclerotic lesions. The cluster of differentiation 36 receptor [CD36 (SR-B2)] plays a key role in atherosclerotic lesion progression and acts as an efferocytic molecule in the resolution of advanced plaque. In previous studies, linear azapeptide CD36 ligands were shown to exhibit anti-atherosclerotic properties. In the present study, a novel potent and selective macrocyclic azapeptide CD36 ligand, MPE-298, has proven effective in protecting against atherosclerosis progression. Features of greater plaque stability were observed after 8 weeks of daily injections with the cyclic azapeptide in apolipoprotein E-deficient mice fed a high-fat high-cholesterol diet.